2015
DOI: 10.3233/jad-150173
|View full text |Cite
|
Sign up to set email alerts
|

Yeast Model of Amyloid-β and Tau Aggregation in Alzheimer’s Disease

Abstract: The amyloid-β peptide (Aβ) and the phosphorylated protein tau have been widely implicated in Alzheimer's disease and are the focus of most research. Both agents have been extensively studied in mammalian cell culture and in animal studies, but new research is focusing on yeast models. Yeast are eukaryotes, just like us, and are amenable to effects and expression of Aβ and tau and appear able to 'report' with considerable relevance on the effects of these biomolecules. The use of yeast enables powerful new appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 76 publications
0
30
0
Order By: Relevance
“…In contrast, the deposition of higher-order tau aggregates within NFTs may be a cellular response aimed at reducing this toxicity [27,29]. This is reminiscent of the situation in amyloid plaques, where the Aß fragments seem to exert their toxic effects more efficiently in the form of soluble oligomeric precursors, rather than in the aggregates found in the amyloid plaques (reviewed in [3,30]). …”
Section: Tau Hyperphosphorylation and Its Relation To Admentioning
confidence: 92%
See 1 more Smart Citation
“…In contrast, the deposition of higher-order tau aggregates within NFTs may be a cellular response aimed at reducing this toxicity [27,29]. This is reminiscent of the situation in amyloid plaques, where the Aß fragments seem to exert their toxic effects more efficiently in the form of soluble oligomeric precursors, rather than in the aggregates found in the amyloid plaques (reviewed in [3,30]). …”
Section: Tau Hyperphosphorylation and Its Relation To Admentioning
confidence: 92%
“…Several excellent reviews have dealt with specific aspects using this model, especially in the study of key AD proteins such as tau and amyloid beta (Aß; see [3,4] and references therein). Here, we will focus on recent advances in the understanding of tauopathies and how baker's yeast has helped to elucidate dis-ease-relevant mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Despite nearly a billion years of evolutionary divergence, recent estimates showed that a fifth of yeast genes have human disease orthologs lending support to functional discovery investigations using this model [92]. Moreover, thanks to amenability of S. cerevisiae to both classical and advanced molecular genetic techniques, to relatively simple, cheap and quick genetic and environmental manipulations, to the large knowledge base and data collections, high-throughput screening technologies and functional genomics that are not possible in humans [93][94][95], this organism has become a valuable and prevalent eukaryotic model organism to unravel complex and fundamental intracellular mechanisms underlying neurodegeneration [96][97][98][99][100][101][102][103][104].…”
Section: Yeast Models For Admentioning
confidence: 99%
“…Furthermore having fewer number of genes compared with the higher eukaryotes makes yeast an ideal model organism to understand the basics of complex cellular processes with less interference of other proteins. Regarding the so‐called misfolding diseases such as Alzheimer's, Parkinson's, Huntington's and prion diseases, conservation of the protein folding system in yeast allows for studying molecular events related to the diseases . Proteins associated with the diseases mentioned can be expressed in yeast and induce protein aggregation and sometimes toxicity similar to their mammalian counterparts.…”
mentioning
confidence: 99%